Pendidikan Islam PENDIDIKAN ISLAM INTEGRATIF MUHAMMAD IQBAL: Menguak Tabir Pendidikan Ideal Perpektif Pujangga Fenomenal - Zainuddin; M. Yunus Abu Bakar; Ah. Zakki Fuad (Qolamuna : Jurnal Studi Islam, 2023)
Muhammad Iqbal is an important figure in the treasury of Islamic culture. He was a philosopher, thinker, scholar, jurist, reformer, politician and above all a poet. Muhammad Iqbal wanted to restore the glory of Islam by connecting Islamic education with philosophy and science as well as modern technological developments. Because for Muhammad Iqbal. Islam is not just a creed, but a way of life that grows and develops, both for individual and social life. Therefore, this article aims to discuss the integrative Islamic education perspective of Muhammad Iqbal's. The research method in this article uses library research. While the research results of this article are the ideal education perspective of Muhammad Iqbal was born from criticism of the Western knowledge hagemony but poor in value, and the stagnation of Eastern (Islamic) knowledge. Education should be a place for individuals to become holistic individuals to achieve Insan Kamil. Muhammad Iqbal's typology of Islamic education includes educational goals, educators, students, curriculum, and learning methods. While the conclusion of this research is that integrative Islamic education according to Muhammad Iqbal, consists of: internal and external, physical and mental, logical and intuition, individual and society, traditional and modern, past, present, and future of life, as well as the balance of the world and the hereafter. As well as things that are pragmatically instrumental or solve life problems. Keywords : Muhammad Iqbal, Integrative Islamic Education